The Digital Indicators Determination for the Period of Cardiac Rest ST and Its Response With Its Extreme Performance Intensity and Its Relationship With the Percentage of Lactic Acid and Blood PH for The Footballers - Sabar Mohammed, Ali; Sabar Mohammed, Majed; Offy Ahmed, Haidar (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in determining numerical indicators to evaluate the periods of the cardiac rest(ST)and the extent of their interaction to the maximum performance of the athlete with the changes that occur in the values of lactic acid and PH blood to maintain the performance of high football players without disruption or fatigue affecting the level of performance accuracy, as for the research problem, the researchers noted that there are no clear numerical indicators for the periods of cardiac rest and their relationship to extreme performance, as well as the lack of knowledge of the relationship of cardiac rest, lactic acid and blood PH during the maximum performance of football players. The research aims to determine the criteria (degrees and standard levels) for the periods of cardiac rest (ST) for footballers at the excellent level in Basra Governorate and also to identify the level of lactic acid and pH blood for football players at the excellent degree in Basra Governorate, learning about the relationship between the periods of cardiac rest (ST) and the level of lactic acid and pH blood of football players at the excellent degree in Basra Governorate. As the research sample has reached 60 players after excluding 9 players representing the goalkeepers in addition to the injured players. The researchers have used the Statistical Package (SPSS) to deal with the data and extract the results that have been obtained from the measurements of the research, as the most important conclusions were finding the criteria (standard levels and degrees) that serve as the objective guide for the assessment of the level of the adaptation and training. Also, the most important recommendation is to adopt the criteria that the researchers have extracted in the evaluation processes of adaptation and training as well as for forecasting and classification selection for football players.